Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s00204-009-0427-x
|View full text |Cite|
|
Sign up to set email alerts
|

Involvement of sensory nerves and TRPV1 receptors in the rat airway inflammatory response to two environment pollutants: diesel exhaust particles (DEP) and 1,2-naphthoquinone (1,2-NQ)

Abstract: The environmental chemical 1,2-naphthoquinone (1,2-NQ) is implicated in the exacerbation of airways diseases induced by exposure to diesel exhaust particles (DEP), which involves a neurogenic-mediated mechanism. Plasma extravasation in trachea, main bronchus and lung was measured as the local (125)I-bovine albumin accumulation. RT-PCR quantification of TRPV1 and tachykinin (NK(1) and NK(2)) receptor gene expression were investigated in main bronchus. Intratracheal injection of DEP (1 and 5 mg/kg) or 1,2-NQ (35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 44 publications
1
21
0
10
Order By: Relevance
“…DEP is a pneumotoxicant that causes pulmonary inflammation and tissue damage, in part, via the activation of pro-inflammatory signaling in the lung through both neurogenic and non-neurogenic pathways (7, 40). However, gene products that detect DEP and initiate specific cellular responses are not well defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DEP is a pneumotoxicant that causes pulmonary inflammation and tissue damage, in part, via the activation of pro-inflammatory signaling in the lung through both neurogenic and non-neurogenic pathways (7, 40). However, gene products that detect DEP and initiate specific cellular responses are not well defined.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have correlated responses to urban PM, including DEP, with activation of airway sensory neurons, particularly C- and Aδ- fibers that express Transient Receptor Potential Ankyrin-1 (TRPA1), TRP Vanilloid-1 (TRPV1), and substance P (37). TRPA1 and V1 are members of the TRP superfamily of ion channels, and numerous TRP receptors including TRPA1, V1–4, and M8 are highly expressed in the respiratory tract where they can function as environmental sensors.…”
Section: Introductionmentioning
confidence: 99%
“…SP was shown to be a potent chemoattractant for basophils through NK1R activation in a human in vitro study (75). With regard to environmental pollution and its biological effect on the airway, diesel exhaust particles were shown to induce edema in the rat trachea and bronchus via the up-regulation of TRPV1, NK1R, and NK2R (76), implying that treatment with receptor antagonists can ameliorate the symptoms caused by air pollutants such as particulate matter < 2.5 μm.…”
Section: Role Of Tks In Hypersensitivity and Inflammation In Airwaymentioning
confidence: 99%
“…It has been shown that components of urban PM, such as diesel exhaust PM (DEP), activate airway neurons that express transient receptor potential (TRP) ankyrin-1 (TRPA1) and TRP vanilloid-1 (TRPV1) (1)(2)(3)(4)(5)(6)(7)(8). TRPA1 and TRPV1 are members of the TRP family of ion channels.…”
mentioning
confidence: 99%
“…TRPA1 and TRPV1, as well as other TRP channels, are expressed by various airway epithelial and alveolar cells in addition to airway neurons. Activation of TRPA1 (10,11), TRPV1 (7,(12)(13)(14)(15)(16)(17), TRPV4 (18), and transient receptor potential cation channel, subfamily M, member 8 (TRPM8) (19) in these cell types by prototypical agonists, select environmental pollutants, and PM also has been demonstrated to cause proinflammatory cytokine/chemokine production and, in some cases, apoptosis.…”
mentioning
confidence: 99%